2019
DOI: 10.3390/su11133535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impacts of Land Use/Cover Change and Rainfall Change on Surface Runoff in China

Abstract: Assessment of the impacts of land use/cover change (LUCC) and rainfall change on surface runoff depth can help provide an understanding of the temporal trend of variation of surface runoff and assist in urban construction planning. This study evaluated the impacts of LUCC and rainfall change on surface runoff depth by adopting the well-known Soil Conservation Service-Curve Number (SCS-CN) method and the widely used Long-Term Hydrologic Impact Assessment (L-THIA) model. National hydrologic soil group map of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Secara nasional di wilayah Cina, rerata tahunan kedalaman limpasan pada tahun 2005, 2010 dan 2015 adalah 78 mm, 83 mm, dan 90 mm. Untuk data penggunaan lahan 2015, karena perubahan curah hujan menyebabkan variasi kedalaman limpasan mulai dari −203 mm hingga 476 mm di berbagai wilayah (Li et al, 2019). Empat komponen utama yang menentukan perubahan keseimbangan air tangkapan di DAS Mbarali-Tanzania adalah curah hujan, pengisian air tanah, penguapan, dan limpasan yang cenderung meningkat (Mutayoba et al, 2018).…”
Section: Limpasan Puncakunclassified
“…Secara nasional di wilayah Cina, rerata tahunan kedalaman limpasan pada tahun 2005, 2010 dan 2015 adalah 78 mm, 83 mm, dan 90 mm. Untuk data penggunaan lahan 2015, karena perubahan curah hujan menyebabkan variasi kedalaman limpasan mulai dari −203 mm hingga 476 mm di berbagai wilayah (Li et al, 2019). Empat komponen utama yang menentukan perubahan keseimbangan air tangkapan di DAS Mbarali-Tanzania adalah curah hujan, pengisian air tanah, penguapan, dan limpasan yang cenderung meningkat (Mutayoba et al, 2018).…”
Section: Limpasan Puncakunclassified
“…The L-THIA-LID 2.1 model was developed from the L-THIA model [37,[42][43][44], which is easy to use and understand and has been successfully applied to many simulation studies of hydrological effects in China [2,45,46]. It has been widely used for the assessment of the implementation effectiveness and cost efficiency of GI practices on runoff control and improvement in many case studies in the U.S. [4,[47][48][49].…”
Section: Model Background 221 Principle and Framework For Gi Practices Simulationmentioning
confidence: 99%
“…Given a lack of observation data in this research area, indirect calibration and validation was conducted. First, based on the research of Li et al [2], the land-use dataset of 2015 (same with the dataset in research of Li et al) and daily rainfall dataset from 2000 to 2017 (same with the rainfall dataset in this study) were used to simulate ARVs of the research area to get the comparison results (Table 4). Secondly, land-use data in this study and rainfall data from 2000 to 2009 were used to simulate ARV from 2000 to 2009 with the L-THIA-LID 2.1 model (baseline scenario, used for model calibration).…”
Section: Model Calibration/validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eaton [17] analyzed a direct runoff reduction method using the L-THIA LID model to analyze green infrastructure screening and reported that direct runoff can be reduced by 12% by using bioretention and raingardens in the watershed. Li et al [18] analyzed changes in the surface runoff caused by land use and rainfall changes using the ArcL-THIA 10.1 model that is based on ArcGIS 10.0 [19]. The authors calibrated the ArcL-THIA 10.1 model by using the baseflow filter program (BFLOW) [20] model to separate direct runoff; they reported that enhanced precipitation contributed more significantly to the observed changes compared to land use during the period 2005-2015.…”
Section: Introductionmentioning
confidence: 99%